2013
DOI: 10.4028/www.scientific.net/kem.549.31
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of the Increase in Titanium Sheets' Drawability

Abstract: Forming of titanium sheets, especially titanium alloy sheets, is very difficult due to low drawability caused by a high ratio of the yield point to the tensile strength Re/Rm, usually more than 90%. Although drawability of titanium sheets can be enhanced by forming at elevated temperatures it is avoided due to the high costs and difficulties associated with the operation of the process. Therefore the authors have developed an unconventional stamping method allowing for forming of almost unworkable materials at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…It should be remembered that forming titanium alloys at increased temperature necessitates solving the problems of its tendency for reacting with oxygen, nitrogen and hydrogen. Absorption of these gases causes unfavourable structural changes and, consequently, deterioration of strength parameters [5,[8][9][10][11][12]. The studies [13][14][15] showed that obtaining greater forming depth is also possible during forming of tailor-welded blanks (TWBs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be remembered that forming titanium alloys at increased temperature necessitates solving the problems of its tendency for reacting with oxygen, nitrogen and hydrogen. Absorption of these gases causes unfavourable structural changes and, consequently, deterioration of strength parameters [5,[8][9][10][11][12]. The studies [13][14][15] showed that obtaining greater forming depth is also possible during forming of tailor-welded blanks (TWBs).…”
Section: Introductionmentioning
confidence: 99%
“…Publications in this field focus primarily on mechanical properties, capability of plastic strain, including methods of determination of forming limit diagrams (FLD) with regards for the effect of anisotropy of mechanical properties, strain rate and temperature as well as opportunities for application of modern methods of forming and optimization of parameters of these processes [1,2,[17][18][19][20][21][22]. Authors of the studies [10] point to a very low, almost zero drawability of sheet metal made of titanium Gr 5 at the temperature of environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various production techniques, only sheet-metal forming enable the production of thin-walled components with high strength [1][2][3][4]. According to [5,6], the tribological properties of the deformed materials and the friction conditions are important factors determining the results of sheet metal forming, particularly in the deep drawing process.…”
Section: Introductionmentioning
confidence: 99%
“…Strain -hardening exponent n, normal anisotropy ratio r and the ratio of yield strength to tensile strength R e /R m are the most essential parameters describing sheet formability [5][6][7][8][9][10][11]. Formability is defined as the sheet -metal ability to be formed into a specific shape without failure.…”
Section: Introductionmentioning
confidence: 99%